Fluid mechanics and thermodynamics of turbomachinery - Dixon, S.L; Hall, C.A (Butterworth-Heinemann, 2014)
Starting with background principles in fluid mechanics and thermodynamics, this title discusses axial flow turbines and compressors, centrifugal pumps, fans, and compressors, and radial flow gas turbines, hydraulic turbines, and wind turbines.